Analysis of the clinical characteristics, drug treatments and prognoses of 136 patients with coronavirus disease 2019. (25th May 2020) - Yang, Qiuxiang; Xie, Ling; Zhang, Wei; Zhao, Lin; Wu, HuaJun; Jiang, Jie; Zou, Jili; Liu, Jianguang; Wu, Jun; Chen, Yonggang; Wu, Jinhu
Abstract: What is known and objective: Since the December 2019 discovery of several cases of coronavirus disease 2019 (COVID‐19) in Wuhan, China, the infection has spread worldwide. Our aim is to report on the clinical characteristics, treatments and prognoses of COVID‐19. Methods: This was a retrospective, single‐centre, case series of 136 patients who were diagnosed with COVID‐19 at Wuhan Third Hospital in Wuhan, China, between 28 January 2020 and 12 February 2020. The clinical characteristics, laboratory tests, treatment features and prognoses were summarized. Results and discussion: The 136 patients were divided into a moderate (M) group (n = 103, 75.7%) and a severe and critical (SC) group (n = 33, 24.3%). There were significant differences in the incidences of concomitant chronic medical illnesses (eg, hypertension, diabetes and cardiovascular disease), fever, dry cough and dyspnoea among the two groups ( P < .05). Compared with those in the M group, lymphocyte count (LYM) decreased significantly in the SC group, while the serum levels of C‐reactive protein (CRP), procalcitonin (PCT), creatinine (Cre), D‐dimer, lactic dehydrogenase (LDH), myoglobin (MB) and troponin I (cTnl) increased significantly in the SC group ( P < .05). The main therapeutic drugs were antivirals, antibiotics, glucocorticoids, immunomodulators, traditional Chinese medicine preparations and symptomatic support drugs. There were significant differences in the incidences of shock, myocardial injury, acute respiratory distress syndrome (ARDS) and renal injury among the two groups ( P < .05). Among the 136 patients, 99 (72.7%) were cured, 14 (10.3%) were transferred to other hospital and 23 (16.9%) died. What is new and conclusion: Elderly patients with chronic diseases are more likely to develop severe or critical COVID‐19 with multiple organ damage or systemic injuries. The improvement of LYM and CRP may be associated with the prognoses of COVID‐19. The combined use of three or more antiviral drugs is to be avoided. The combination of broad‐spectrum antibacterial drugs is not recommended and the risk of drug‐induced liver injury should be monitored. Throughout a patient's hospitalization, their treatment plan should be evaluated and adjusted according to their vital signs, clinical symptoms, laboratory tests and imaging changes. Patients should receive effective psychological counselling. Abstract : Elderly patients with chronic diseases are more likely to develop severe or critical COVID‐19 with multiple organ damage or systemic injuries. The improvement of LYM and CRP may be associated with the prognoses of COVID‐19.